Review of Affirmative Action Policy in West Java DPRD: challenges and Solutions of Political Parties in Achieving Women's Representation - Wulandari, Rafih Sri; Kartini, Dede Sri; Alamsah D, Nandang; Santoso, Eko Budi (Journal of Ecohumanism, 2024)
This study tries to analyze the performance of affirmative action policies for female participation in the Regional House of Representatives (DPRD) of West Java Province, focused on three principal political parties: PDIP, Golkar, and PKS. Notwithstanding the implementation of a 30% female quota, women's representation in parliament has yet to attain an ideal percentage. This study applies a qualitative methodology utilizing explanatory and descriptive approaches, concentrating on the strategies utilized by each party to recruit and assist female parliamentary candidates. The results indicate that although PDIP, Golkar, and PKS are dedicated to affirmative action programs, their execution is shaped by varying ideological perspectives and socioeconomic circumstances. PDIP employs an inclusive strategy to enhance female representation but encounters challenges posed by conservative local cultures. Golkar prioritizes electoral efficacy by selecting pragmatic candidates, focusing on women with robust political networks, while PKS adheres to religious principles that constrain women's political participation. The findings indicate that affirmative action programs must be tailored to local dynamics and party beliefs to effectively enhance meaningful female representation in parliament. The study indicates that while affirmative action fosters female representation, its effectiveness relies on the adaptive strategies of each party in tackling local obstacles.